Gambaran Kondisi Kesehatan Lingkungan Pasar dan Tingkat Kepadatan Lalat di Pasar Tradisional Kota Kupang - Desriani M. J. U. Pati; Mustakim Sahdan; Cathrin W. D. Geghi; Agus Setyobudi (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Health checks in the market are an effort to determine the condition of a clean, safe, comfortable and healthy market environment. An unhealthy market will increase the density of flies which will have an impact on the transmission of fly-based diseases in the market. The purpose of this study was to determine the description of the health conditions of the market environment and the density of flies in the Traditional Markets of Kupang City. The type and design of the research used was descriptive research with a survey method. This research was conducted at the Traditional Markets of Kupang City in September-October 2024. The population in this study was the Traditional Markets in Kupang City. The samples in this study were Oebobo Market, Kasih Naikoten Market and Oeba Market. Data analysis was conducted descriptively, The results of the study showed that from 124 assessment variables obtained a total score of yes for Oebobo Market of 58 (46.77%), a total score of yes for Kasih Naikoten Market of 50 (40.32%) and a total score of yes for Oeba Market 44 (35.48%) with the third category of markets not meeting the requirements of a healthy market and the results of measuring the level of fly density at the Kupang City Traditional Market with each Market 3 points determined namely Meat Stall, Raw Fish Stall and Trash bin at Oebobo Market obtained an average fly density of 6 tails/blockgrill, at Kasih Naikoten Market the average fly density was 10 tails/blockgrill and at Oeba Market the average fly density was 9 tails/blockgrill with a high fly density category. Therefore, cooperation is needed between the government and the local community to maintain each other and create a healthy and clean market environment to avoid disease.